Effect of Maize Stover in Fermented Total Mixed Ration on Nutritive Value and Digestibility Quality in Vitro - R. Buddanoi; A. Abrar; C. Wachirapakorn (Jurnal Peternakan Sriwijaya, 2017)
The objective of this experiment was to investigate the effect of maize stover used as roughage source in fermented total mixed ration on nutritive value and digestibility quality by in vitro technique. The experimental compared between the feeds non-fermented total mixed ratio (TMR) group and fermented total mixed ratio (FTMR) group by fermentation 21 days, each group were ratio 60:40 and five replications. The results revealed that CF content of FTMR increased from 33.79% to 40.70% significantly different (P<0.05) and DM, CP, EE and ash were not significantly different between treatments (P>0.05). The digestibility quality were dry matter digestibility (%DMD) in FTMR higher than control group significantly different (P<0.05). Moreover total volatile fatty acids (VFAs) in FTMR increased from 15.00 to 39.50 mM higher than control group not significantly different (P>0.05) and N-NH3 concentrations were not significantly different (P>0.05). The gas production was recorded at 0, 6, 12, 18, and 24h of incubation. The cumulative gas production curve both of treatments was remarkable boost from 0h to 6h incubation of FTMR from 57.5 to 37 ml and then incubation time the cumulative gas production both of them were slowly decrease.